Consumer Deceleration - Husemann, Katharina C; Eckhardt, Giana M (Journal of Consumer Research, 2019)
AbstractPeople increasingly seek out opportunities to escape from a sped-up pace of life by engaging in slow forms of consumption. Drawing from the theory of social acceleration, we explore how consumers can experience and achieve a slowed-down experience of time through consumption. To do so, we ethnographically study the Camino de Santiago pilgrimage in Spain and introduce the concept of consumer deceleration. Consumer deceleration is a perception of a slowed-down temporal experience achieved via a decrease in certain quantities (traveled distance, use of technology, experienced episodes) per unit of time through altering, adopting, or eschewing forms of consumption. Consumers decelerate in three ways: embodied, technological, and episodic. Each is enabled by consumer practices and market characteristics, rules, and norms, and results in time being experienced as passing more slowly and as being an abundant resource. Achieving deceleration is challenging, as it requires resynchronization to a different temporal logic and the ability to manage intrusions from acceleration. Conceptualizing consumer deceleration allows us to enhance our understanding of temporality and consumption, embodied consumption, extraordinary experiences, and the theory of social acceleration. Overall, this study contributes to consumer research by illuminating the role of speed and rhythm in consumer culture.